The impact of Japanese occupation in the writings of Malaysian Indian writers - Mani, Manimangai; Veeraputhran, Veeramohan (Center for Resource, Research and Publication Services, 2017)
The Japanese occupation in Malaya from 1942 -1945 during the World War Two has scarred the lives of many people. The victims and their descendents were haunted by the memories of the Japanese atrocities for decades. These untold cruelties committed by the Japanese army towards the Malayan people is often used as the theme by Malaysian Indian writers in their works. The struggle of the Indians during this period is narrated in most of the novels that has WW2 as a setting either it is written in English or Tamil language. The aim of this study is to show why Malaysian Indian writers often use the theme of war in their novels. This study will analyse two novels; Rani Manicka’s, The Rice Mother (2002) which is written in English and Siam Marana Rayil (1993) by R. Shanmugam which is in Tamil. Both writers have used war as their setting and harp on the same issue which depicts the hardships faced by the people during the Japanese occupation. Their works will be analysed to highlight the sufferings encountered by the Malayan people especially the Indians during that period. It will also reveal the motive of these writers in using this theme in their works.Finally, this study will also show how these writings can be regarded as historical records for the Indians in Malaysia.